ANALISIS INSTRUMEN PENILAIAN KEMAMPUAN PEMODELAN MATEMATIS PADA KELAS FISIKA MENGGUNAKAN RASCH MODEL - Desy Kumala Sari (MEGA: Jurnal Pendidikan Matematika, 2020)
Mathematical modeling was the ability to formulate natural laws into mathematical form. This ability was very important to support learning in fields related to calculations such as mathematics, physics, and chemistry. This research includes development research. The product developed as an instrument of mathematical modeling ability assessment in physics class. This instrument was analyzed and adjusted for the Rasch model. The variables that were used as a reference are validity, difficulty level, and reliability. Based on the analysis results, the MNSQ INFIT value of 1.01 Â± 0.18 was obtained, which means that the developed instrument was compatible with the Rasch model so that the valuation instrument was declared valid. The level of difficulty in the analysis results obtained results of 0.00 Â± 0.71 which means that the questions developed were mostly in the medium category. Furthermore, the reliability of the assessment instruments developed was 0.93, which means that the reliability of the developed assessment instruments was in the excellent category.